Consumer packaging as a tool for social and ethical marketing - Lialiuk, Alla; Kolosok, Andrii; Skoruk, Olena; Hromko, Liliia; Hrytsiuk, Nataliia (LLC “Consulting Publishing Company “Business Perspectives”, 2019)
Producing consumer packaging, which would meet the modern requirements in a comprehensive manner, while ensuring the needs of a consumer, a manufacturer and society as a whole, is currently one of the most important issues. In the context of developing a socially responsible society, the transition from classical marketing schemes to the social and ethical marketing is important for producers. The article defines the features of consumer packaging as a marketing tool based on theoretical generalization and survey among the city of Lutsk residents. The author’s vision of the packaging strategy and the product strategy interaction in the context of socially oriented marketing is presented. The possible options of packaging recycling are outlined: use of returnable packaging; utilization of packaging and the use of appropriate materials that are subject to recycling; use of packaging for other purposes.
Keywords: environmental marketing; packaging strategy; product strategy; environmental responsibility; packaging recycling; М30; M31